2017
DOI: 10.1074/jbc.m117.805200
|View full text |Cite
|
Sign up to set email alerts
|

Iron is a substrate of the Plasmodium falciparum chloroquine resistance transporter PfCRT in Xenopus oocytes

Abstract: The chloroquine resistance transporter of the human malaria parasite , PfCRT, is an important determinant of resistance to several quinoline and quinoline-like antimalarial drugs. PfCRT also plays an essential role in the physiology of the parasite during development inside erythrocytes. However, the function of this transporter besides its role in drug resistance is still unclear. Using electrophysiological and flux experiments conducted on PfCRT-expressing oocytes, we show here that both wild-type PfCRT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Therefore, the vacuolar side of PfCRT may play an important role in substrate recognition and/or transport, which supports the hypothesis of a physiological substrate being expelled by PfCRT out of the parasite DV. This is in line with the observation that recombinant PfCRT, either reconstituted in proteoliposomes 25 or expressed at the surface of Xenopus laevis oocytes 13,26 , directionally transports CQ, peptides, basic amino acids, and ferric/ferrous iron. In the parasite, these solutes are known to accumulate in the DV from which they could be transported out either solely by mutant PfCRT (CQ and PPQ in their protonated forms) or by WT and/or mutant PfCRT (peptides, basic amino acids, and ferric/ferrous iron).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the vacuolar side of PfCRT may play an important role in substrate recognition and/or transport, which supports the hypothesis of a physiological substrate being expelled by PfCRT out of the parasite DV. This is in line with the observation that recombinant PfCRT, either reconstituted in proteoliposomes 25 or expressed at the surface of Xenopus laevis oocytes 13,26 , directionally transports CQ, peptides, basic amino acids, and ferric/ferrous iron. In the parasite, these solutes are known to accumulate in the DV from which they could be transported out either solely by mutant PfCRT (CQ and PPQ in their protonated forms) or by WT and/or mutant PfCRT (peptides, basic amino acids, and ferric/ferrous iron).…”
Section: Discussionsupporting
confidence: 88%
“…Its secondary structure, location in the DV membrane and belonging to the Drug/Metabolite Transporter (DMT) superfamily support its participation in metabolite transport 10,24 . PfCRT was reported as a proton-coupled transporter recognizing some cationic substrates 25 , a Fe 2+ /Fe 3+ transporter 26 , and playing a role in glutathione homeostasis 27,28 . Earlier studies have also reported PfCRT as a Cl − channel mediator, a proton pump regulatory and an activator of Na + /H + exchangers [29][30][31] .…”
mentioning
confidence: 99%
“…They play vital roles in housekeeping, gene expression and other cellular processes and are targeted by antimalarial drugs 38 , 39 . Moreover, iron homeostasis is essential for erythrocytic development and is implicated in drug mechanisms of quinolines 40 , 41 , same drug family like Lumefantrine. We therefore selected the SNP within the Pfnfs for an initial analysis of temporal changes in allele frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying native function of PfCRT remains unclear, with studies suggesting that PfCRT might transport glutathione, Cl − ions, H + ions, or a range of cationic substrates including hemoglobin (Hb)-derived amino acids or peptides 10 , 19 , 23 27 . A recent study using PfCRT-expressing Xenopus laevis oocytes also provided evidence that iron may be a substrate of PfCRT 28 . Transport studies also suggest that PfCRT mutations can enable this electrochemical potential-driven transporter to mediate the facilitated diffusion of protonated CQ, which itself might also bind to and inhibit PfCRT 10 , 12 , 15 , 21 , 29 .…”
Section: Introductionmentioning
confidence: 95%
“…Given our initial findings, we sought to further investigate the effect of the PfCRT L272F mutation. Previously, PfCRT isoforms have been associated with altered Hb catabolism in the DV 26 , 28 . Hb is present at low millimolar concentrations in the RBC cytoplasm and is imported into the DV via cytostomes or endocytic vesicles 42 , 43 .…”
Section: Introductionmentioning
confidence: 99%